AB016. Transurethral PlasmaKinetic enucleation of prostate versus transurethral PlasmaKinetic resection of prostate for benign prostate hyperplasia - Sun, Ting (Transl Androl Urol, 2016)
BACKGROUND: To compare the efficacy and safety of transurethral PlasmaKinetic enucleation of prostate (PKEP) versus transurethral PlasmaKinetic resection of prostate (PKRP) for benign prostate hyperplasia. METHODS: The Prospective and randomized controlled trials (RCTs) pertaining to PKEP and PKRP for benign prostate hyperplasia were retrieved from PubMed, Wanfang and so on. The level of trials was assessed by using Cochrane system. RESULTS: Compared with PKRP, the time of operation shorten 10.17 min, the time of catheterization and hospital stay shorten 22.30 h, 1.33 d respectively. The volume of intraoperative bleeding decreased 47.34 mL. The quantity of resectable prostate increase 10.76 g, difference is statistically significant (P<0.05). Compared with PKRP, the international prostate symptom score (IPSS) was lower after 3 months, the quality of life (QOL) and residual urine volume (RUV) was lower after 6 months, the maximum floe rate (Q(max)) was higher after 3 and 6 months, difference is statistically significant (P<0.05). No significant differences were found in IPSS, QOL, Q(max), RUV, international index of erectile function 5 (IIEF-5) between PKRP and PKEP after 1 and 2 years. The incidence of transfusion and capsular perforation was lower than PKRP, but the incidence of postoperative Transient urinary incontinence was higher than PKRP. CONCLUSIONS: Compared with PKRP, PKEP cause less blood loss and requires a shorter operation time, a shorter catheterization time and a shorter hospital stay. It resects the proliferated prostate more cleanly with lower incidence of capsular perforation, but the incidence of postoperative transient urinary incontinence was higher. The short-term efficacy of PKEP was better than PKRP, but no significant differences were found in long-term efficacy and the postoperation influence of sex function between PKEP and PKRP.